Guru Sebagai Agen Perubahan: Peran Guru dalam Meningkatkan Mutu Pendidikan - Elmumtazah, Devi Harisah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to describe the role of teachers as agents of change in improving the quality of education at SD Negeri 244 Palembang. Through a qualitative approach with a case study method, this study involved 15 teachers as participants. Data collection was carried out through in-depth interviews, observations, and documentation. The results of the study indicate that teachers have a very important role in improving the quality of education through various activities, such as innovation in learning, self-development, and collaboration with other parties. However, there are several obstacles faced by teachers in carrying out their role as agents of change. This study concludes that teachers have a very important role as agents of change in improving the quality of education. To support the role of teachers as agents of change, various efforts are needed, such as: Continuous professional development, providing opportunities for teachers to participate in relevant training and professional development. Support from the school, providing adequate support for teachers in carrying out their duties, such as providing complete facilities and creating a conducive work environment. Collaboration with various parties, building cooperation with parents, communities, and the government to create synergy in improving the quality of education. This study has implications for teacher professional development and education policy.